Oxaliplatin Eluting CalliSpheres Microspheres for the Treatment of Unresectable or Recurrent Hepatocellular Carcinoma - Bi, Yonghua; Ren, Kewei; Ren, Jianzhuang; Ma, Ji; Han, Xinwei (Frontiers in Pharmacology, 2022)
Aim: Drug-eluting beads-transarterial chemoembolization (DEB-TACE) has been widely used in unresectable and advanced hepatocellular carcinoma (HCC). However, no study reported the clinical outcomes of drug-eluting beads TACE (DEB-TACE) with oxaliplatin-eluting CalliSpheres microspheres in the treatment of HCC. This study reports the preliminary outcomes of DEB-TACE loaded with oxaliplatin for the treatment of patients with unresectable or recurrent HCC. Methods: From November 2019 to November 2021, 29 patients with unresectable or recurrent HCC were recruited from our department and treated by DEB-TACE loaded with oxaliplatin. The primary endpoint was progression-free survival (PFS), and the secondary endpoints were disease control rate and safety. Tumor response was investigated at 1, 3, and 6 months after DEB-TACE according to the criteria of the response evaluation in solid tumor (RECIST) criteria and the modified RECIST criteria (mRECIST). Survival curve was generated with the Kaplan–Meier method. Results: A total of 49 DEB-TACE sessions were performed, with a technical success rate of 100%. The overall response rate and disease control rate were 52.4 and 95.2%, 64.7 and 76.5%, and 54.5 and 63.3%, respectively, at 1, 3, and 6 months after DEB-TACE (mRECIST). The PFS was 5.9 months, and the median overall survival was 18.8 months. The 6- and 12-month overall survival rate was 82.5% and 67.5%, respectively, No treatment-related mortality or severe adverse events were observed. Minor complications were observed in 21 patients (72.4%), and abdominal pain (41.4%) was the most common treatment-related complication. Conclusion: DEB-TACE loaded with oxaliplatin-eluting CalliSpheres microspheres could be a safe, feasible, and efficacious palliative regimen in unresectable or recurrent HCC patients.